Studies on Children With Developmental Coordination Disorder in the Past 20 Years: A Bibliometric Analysis via CiteSpace - Wu, Mei-Qin; Wu, De-Qing; Hu, Chun-Ping; Iao, Lai-Sang (Frontiers in Psychiatry, 2021)
ABSTRACT: Children with developmental coordination disorder (DCD) have been commonly observed and drawn an increasing amount of attention over the past decades. The aim of the present study is to evaluate the origin, current hotspots and research trends on children with DCD using a bibliometric tool. After searching with “children” and “developmental coordination disorder” as the “topic” and “title” words, respectively, 635 original articles with 12559 references were obtained from the electronic databases, Web of Science Core Collection (WoSCC). CiteSpace V.5.7.R2 was used to perform the analysis. The number of publications in this field was increasing over the past two decades. John Cairney from the Department of Family Medicine, McMaster University, Canada was found to be the most productive researcher. Meanwhile, McMaster University and Canada was the most productive research institution and country, respectively. References and journals co-citation analysis revealed the top landmark articles and clusters in this field. Clumsiness was the most strength burst keyword. Moreover, task, meta-analysis, difficulty, adult, and impact will be the active research hotspots in future. These findings provide the trends and frontiers in the field of children with DCD, and valuable information for clinicians and scientists to identify new perspectives with potential collaborators and cooperative countries.